Mitochondrial DNA reveals unexpected diversity of chubs (genus Squalius; Cypriniformes, Actinopterygii) in the Adriatic basin - Ivana Buj; Marko Ćaleta; Pero Tutman (Frontiers in Marine Science, 2015)
The genus Squalius comprises more than 40 species inhabiting various freshwater habitats. They are distributed in Europe and Asia, with particularly high diversity recorded in the Mediterranean area. The taxonomic status of many populations is still matter of debate. With this investigation we aimed to help in resolving taxonomic uncertainties of the chubs distributed in the Adriatic basin in Croatia and Bosnia and Herzegovina. Phylogenetic reconstruction based on mitochondrial gene for cytochrome b revealed high diversity of chubs in the investigated area. Two evolutionary independent lineages are revealed: the first one comprising species Sq. svallize, Sq. tenellus, Sq. illyricus and Sq. zrmanjae; whereas the second lineage corresponds with Sq. squalus. High intraspecific structuring of Sq. squalus was detected, implying necessity of taxonomic revision of that species. Based on the obtained results, most important aspects of the evolutionary history of the genus Squalius in the Adriatic basin will be discussed and evolutionary significant units identified.